Cranial nerves in the Australian lungfish, Neoceratodus forsteri, and in fossil relatives (Osteichthyes: Dipnoi). Issue 1 (February 2017) - Kemp, A.
Graphical abstract: Highlights: Cranial nerves form before skeletal structures develop. Cranial nerves I, II, V, VIII are sensory; VII, IX and X are mixed. Nerve V has a plexus between two anterior branches. Nerve V has a recurrent link with nerves IX and X. The tubules of fossil lungfish are not neural. Abstract: Three systems, two sensory and one protective, are present in the skin of the living Australian lungfish, Neoceratodus forsteri, and in fossil lungfish, and the arrangement and innervation of the sense organs is peculiar to lungfish. Peripheral branches of nerves that innervate the sense organs are slender and unprotected, and form before any skeletal structures appear. When the olfactory capsule develops, it traps some of the anterior branches of cranial nerve V, which emerged from the chondrocranium from the lateral sphenotic foramen. Cranial nerve I innervates the olfactory organ enclosed within the olfactory capsule and cranial nerve II innervates the eye. Cranial nerve V innervates the sense organs of the snout and upper lip, and, in conjunction with nerve IX and X, the sense organs of the posterior and lateral head. Cranial nerve VII is primarily a motor nerve, and a single branch innervates sense organs in the mandible. There are no connections between nerves V and VII, although both emerge from the brain close to each other. The third associated system consists of lymphatic vessels covered by an extracellular matrix of collagen, mineralised as tubules in fossils. Innervation of the sensory organs is separate from the lymphatic system and from the tubule system of fossil lungfish.